The effectiveness of inhaled ginger essential oil in improving dietary intake in breast‐cancer patients experiencing chemotherapy‐induced nausea and vomiting. Issue 1 (25th April 2016) - Salihah, Noor; Mazlan, Nik; Lua, Pei Lin
Abstract: Background: Evidence suggests the use of complementary therapies may help in relieving the adverse effects of cancer‐related treatment, including nausea. Objectives: To evaluate the effectiveness of inhaled ginger essential oil (EO) in improving dietary intake in women with breast cancer experiencing chemotherapy‐induced nausea and vomiting (CINV). General perception on the use of ginger aromatherapy was also evaluated. Methods: A single‐blind, randomised, placebo‐controlled, crossover study was conducted in two oncology clinics in Peninsular Malaysia. Women received 5 days of aromatherapy treatment using either ginger EO or fragrance‐matched placebo [ginger fragrance oil (FO)] in an order dictated by the treatment group sequence. The following aspects were evaluated: nutritional status (BMI, nutritional requirement, dietary intake) and general perception of aromatherapy. Results: Sixty women completed the study (age=47.3±9.26 years; receiving highly emetogenic chemotherapy=86.7%; BMI=25.5±5.4 kg/m 2 ). Energy intakes were significantly higher after patients were treated with ginger EO than ginger FO at day 3 ( P =0.015) and day 5 ( P =0.002). Significant improvements in energy intake were also observed over time [ F (2, 57)=54.21, P <0.001], reaching almost 90% of the energy requirement 5 days' post‐chemotherapy. Inhaled aromatherapy using ginger EO was rated marginally more helpful than the ginger FO (63.3% vs. 61.6%). Being delivered via a necklace, the treatment method was considered feasible for participating women. Conclusion: The use of inhaled ginger EO for CINV could possibly help patients resume their dietary intake. This complementary treatment was also favourably received by the participating women.